Financial mechanisms and economic effects of sports in modern Russia - Namazov, A.K.; Ragozina, N.A.; Kashin, S.M.; Mukhina, A.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the financial mechanisms and economic effects of the functioning of sport in modern Russia. Methods and structure of the study. The research was carried out on the basis of a systematic approach using economic-statistical methods, analysis of official data from the Ministry of Sport of the Russian Federation, federal budget reports and market indicators of the fitness industry for the period 2019–2025. Results and conclusions. The economic significance of sport manifests through multiple mechanisms: the generation of direct revenues from paid services, the provision of jobs in related industries (tourism, retail, media), the influence on labour productivity through improving public health, as well as social effects associated with the prevention of socially significant diseases. Thus, the objective of this study is a comprehensive analysis of the economics of sport as part of the service sector and the disclosure of the mechanisms of functioning of commercial and non-commercial aspects of sporting activities in Russia [6]. Sport in Russia functions as a multi-level economic system in which state investments in non-commercial sport and support for youth programmes create the foundation for the development of the commercial sports industry. This interaction generates both direct economic effects (job creation, tax revenues) and significant indirect and social effects (improvement of public health, reduction of socially negative phenomena and development of human capital).